Kepatuhan Pemerintah Jerman terhadap ICERD dalam Upaya Pemberantasan Diskriminasi Rasial di Jerman - Giorgio Alfari Hendri; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2020)
This research aims to explain Germany’s compliance with the ICERD in its efforts to eradicate racial discrimination in Germany. Racial discrimination is one of the problems that has ingrained in Germany. An increase in immigration flows in the past few decades has led Germany to a fear of an increase in racial discrimination activities in Germany. This prompted the Federal Government of Germany to take efforts in eliminating racial discrimination through the ICERD where these efforts have been regulated in the indicators that are listed in the ICERD. This research uses compliance theory in analysing Germany’s compliance with the ICERD. This research tries to explain the relevance of ICERD in Germany’s efforts to eradicate racial discrimination. This research also tries to explain the efforts of the Federal Government of Germany in complying with the ICERD and its compliance level. At the end of this paper, the author presents the results of this research which reveals that ICERD is still relevant in the fight against racial discrimination in Germany. Moreover, this study also reveals the Federal Government of Germany’s treaty-induced compliance with the ICERD.